Diagnosis and nursing activities for the care of patient with Crohn's disease - Antonia Mauryane Lopes, Ana Paula Cardoso Costa, Grazielle Roberta Freitas da Silva, Amanda Delmondes de Brito Fontenele Fernandes (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.8245-51